COVID-19 and its continuing burden after 12 months: a longitudinal observational prospective multicentre trial. Issue 2 (13th March 2023) - Sahanic, Sabina; Tymoszuk, Piotr; Luger, Anna K.; Hüfner, Katharina; Boehm, Anna; Pizzini, Alex; Schwabl, Christoph; Koppelstätter, Sabine; Kurz, Katharina; Asshoff, Malte; Mosheimer-Feistritzer, Birgit; Coen, Maximilian; et al.
Background: Recovery trajectories from coronavirus disease 2019 (COVID-19) call for longitudinal investigation. We aimed to characterise the kinetics and status of clinical, cardiopulmonary and mental health recovery up to 1 year following COVID-19. Methods: Clinical evaluation, lung function testing (LFT), chest computed tomography (CT) and transthoracic echocardiography were conducted at 2, 3, 6 and 12 months after disease onset. Submaximal exercise capacity, mental health status and quality of life were assessed at 12 months. Recovery kinetics and patterns were investigated by mixed-effect logistic modelling, correlation and clustering analyses. Risk of persistent symptoms and cardiopulmonary abnormalities at the 1-year follow-up were modelled by logistic regression. Findings: Out of 145 CovILD study participants, 108 (74.5%) completed the 1-year follow-up (median age 56.5 years; 59.3% male; 24% intensive care unit patients). Comorbidities were present in 75% (n=81). Key outcome measures plateaued after 180 days. At 12 months, persistent symptoms were found in 65% of participants; 33% suffered from LFT impairment; 51% showed CT abnormalities; and 63% had low-grade diastolic dysfunction. Main risk factors for cardiopulmonary impairment included pro-inflammatory and immunological biomarkers at early visits. In addition, we deciphered three recovery clusters separating almost complete recovery from patients with post-acute inflammatory profile and an enrichment in cardiopulmonary residuals from a female-dominated post-COVID-19 syndrome with reduced mental health status. Conclusion: 1 year after COVID-19, the burden of persistent symptoms, impaired lung function, radiological abnormalities remains high in our study population. Yet, three recovery trajectories are emerging, ranging from almost complete recovery to post-COVID-19 syndrome with impaired mental health. 1  year after #COVID19, 51% show radiological abnormalities and 33% show functional lung impairment. Yet, three recovery trajectories are emerging, ranging from almost complete recovery to post-COVID syndrome with impaired mental health. https://bit.ly/3gYbNQq